The stability of money demand and monetary transmission mechanism in Thailand - Raksong, Saranya (Curtin University, 2010)
The major objective of this thesis is to investigate whether there exists a stable long run and short run equilibrium relationship between real money balances (M1 or M2) and their determinants in Thailand. A cointegration analysis and the Vector Error Correction Model (VECM) are conducted on quarterly data over two data set periods, 1980Q1 to 2007Q1 and 1993Q1 to 2007Q1. The results indicate that there exists a long run equilibrium relationship between real money demand (both M1 and M2) and its determinants: real income, price level, exchange rates, and external interest rates.The thesis also used the Vector Autoregression model (VAR) to test the monetary transmission mechanism in Thailand in three different channels of monetary policy: the interest rate channel, the credit channel, and the exchange rate channel. The results find that a change in the M1 money demand has more effect on economic growth while a change in M2 has a stronger effect on the price level. In addition, the results also show that the M1 money demand is responsive to the transmission mechanism in all channels tested in the thesis.